The First Pelvic Exenteration in West Sumatera : A Case Report - Ayu Anissa Bahri; Syamel Muhammad (Universitas Andalas, 2022)
Introduction: Pelvic exenteration (PE) is an ultra-radical surgical procedure introduced by Alexander Brunschwig in 1948, which a way for symptomatic palliative care in subjects with advanced gynecological malignancies that do not respond to radiation therapy, who experience subsequent complications including fistula, infection, or pain. Objective: The aim of this case report is to share our first experience of pelvic exenteration in patient with recurrent cervical cancer in West Sumatera. Case Report: We report the case of a 42-year-old woman, who was diagnosed with a progressive recurrent cervical cancer that had been treated with a radiotheraphy for cervical cancer stage IIIB and adjuvant chemotherapy. The patient was planned for pelvic exenteration. Prior to surgery, patient had done several preparations such as ultrasound, CT scan, laboratory tests, urologist and colorectal surgeon consult. The patient had undergone a supralevator pelvic exenteration by gynecologic oncologist, urologist and colorectal surgeon. The supralevator exenteration pelvic included total hysterectomy, bilateral salpingo-oophorectomy, cystectomy, and Miles procedure. The reconstruction process included ileal conduit and colostomy. Conclusions: Pelvic exenteration can be done with good teamwork between gynecologic oncologist, urologist, colorectal surgeon with postoperative complications (hypoalbuminemia and low intake) can be tolerated.Keywords: supralevator pelvic exenteration, cervical cancer